Preparation method of aluminum alloy profile with antifouling wear-resistant coating
By using composite polyamic acid and modified silica and other materials to prepare powder coatings, the problem of insufficient anti-fouling and wear-resistant coating performance of aluminum alloy profiles is solved, and higher wear-resistant, anti-fouling and anti-UV aging performance is achieved.
Patent Information
- Application Number
- CN202411813851.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-28
AI Technical Summary
The anti-fouling and wear-resistant coatings of existing aluminum alloy profiles are insufficient in terms of anti-fouling, anti-wear and UV resistance, and are susceptible to pollution and wear.
Powder coatings are prepared by composite polyamic acid, modified silica, polymethyl methacrylate and 1H,1H,2H,2H-perfluorodecyl mercaptan, and anti-fouling and wear-resistant coatings are formed through surface treatment, electrostatic spraying and high-temperature treatment.
It significantly improves the wear resistance, stain resistance and UV aging resistance of the surface of aluminum alloy profiles, and enhances the adhesion strength and hydrophobic properties of the coating.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of antifouling and wear-resistant profile processing, and in particular to a method for preparing an aluminum alloy profile with an antifouling and wear-resistant coating. Background Art
[0002] As a lightweight, high-strength material, aluminum alloy profiles have been widely used in aerospace, transportation, architectural decoration and other fields due to their good processing performance and corrosion resistance. During use, especially in outdoor environments, aluminum alloy profiles are easily corroded by pollutants such as dust, rain, grease, etc. These pollutants not only affect their appearance, but may also accelerate the corrosion process. In addition, although aluminum alloy has good strength and toughness, its hardness is relatively low and it is susceptible to friction and wear.
[0003] In order to improve the wear resistance and anti-fouling properties of aluminum alloy profiles, a wear-resistant coating is usually formed on the surface of the aluminum alloy profile. Powder coating spraying, as an efficient and environmentally friendly coating technology, is widely used in the coating preparation of aluminum alloy profiles. Compared with traditional solvent-based coatings, powder coatings have the advantages of no solvent, no wastewater, no exhaust gas emissions, etc., which meets modern environmental protection requirements.
[0004] The powder coating in the prior art has relatively good anti-corrosion performance, but its oleophobic and hydrophobic anti-fouling performance needs to be further improved. In addition, when protecting aluminum alloy profiles, inorganic nanomaterials are usually added to the powder coating to improve the wear resistance of the coating. However, due to the difference in polarity between the materials, the addition of inorganic nanomaterials will reduce the strength of the powder coating, and the powder coating itself has poor aging resistance. When in use, the wear-resistant coating on the surface of the aluminum alloy profile is easily aged and denatured by ultraviolet rays, causing the coating to fall off and deform. The wear resistance, anti-fouling and anti-ultraviolet performance of the coating need to be further improved.
[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing an aluminum alloy profile with an anti-fouling and wear-resistant coating, so as to solve the technical problem in the prior art that the wear resistance, anti-fouling and anti-ultraviolet performance of the anti-fouling and wear-resistant coating of the aluminum alloy profile need to be further improved.
[0007] The object of the present invention can be achieved by the following technical scheme: A method for preparing an aluminum alloy profile with an anti-fouling and wear-resistant coating comprises the following steps: S1. Surface treatment is performed on the aluminum alloy profile to obtain a pre-treated profile; S2, adding composite polyamic acid, modified silica, polymethyl methacrylate and 1H,1H,2H,2H-perfluorodecyl mercaptan into a ball mill, transferring to a reaction kettle after ball milling for 12-14 hours, heating until the system is melted, cooling and solidifying, crushing, and passing through a 300-mesh sieve to obtain a powder coating; S3, using a powder electrostatic spraying method, spraying powder coating on the surface of the pretreated profile, transferring it to a drying oven at a temperature of 140-160°C, drying it for 2-3 hours, and forming a polyamic acid coating with a thickness of 0.5-0.7mm on the surface of the aluminum alloy profile; S4. Place the aluminum alloy profile with polyamic acid coating in a modification liquid with a temperature of 40-50°C, soak for 2-3 hours, take it out, wash the surface with purified water, and perform heat treatment to form an antifouling and wear-resistant coating on the surface of the aluminum alloy profile.
[0008] Furthermore, the surface treatment in step S1 includes the following steps: A1. Soak the aluminum alloy profile in 2wt% nitric acid at a temperature of 55-65°C for 30-50 minutes, remove the aluminum alloy profile, wash it with purified water until it is neutral, and then ultrasonically clean the aluminum alloy profile with acetone and ethanol for 20 minutes in sequence to obtain a pre-treated profile; A2. Spray the KH-560 solution on the pre-treated profile, place it at room temperature for 30-50 minutes, clean the profile surface with purified water and then dry it to obtain the pre-treated profile, wherein the KH-560 solution is composed of KH-560, anhydrous ethanol and 0.2 mol / L sodium hydroxide solution in a dosage ratio of 5g:20mL:6mL.
[0009] The preparation principle of pre-treated profiles is: By soaking in nitric acid, the oil, oxides and other impurities on the surface of the aluminum alloy profile are removed to provide a clean and uniform surface for subsequent coating adhesion. After the KH-560 solution is sprayed on the aluminum alloy surface, the siloxane groups react with the active reactive groups on the aluminum alloy surface to form chemical bonds, fully reacting and fixing KH-560 on the aluminum alloy surface to prepare a pretreated profile.
[0010] Furthermore, in step S2, the weight ratio of composite polyamic acid, modified silica, polymethyl methacrylate and 1H,1H,2H,2H-perfluorodecyl mercaptan is 40-50:10-15:15-20:6-8; in step S4, the modifying liquid is an 8-10wt% titanic acid aqueous solution, and the heat treatment method is: placing the aluminum alloy profile in a tubular furnace, raising the temperature of the tubular furnace to 270-280°C, and heat-insulating treatment for 2.5-3.5h.
[0011] Furthermore, the preparation method of the composite polyamic acid is as follows: 4,4'-oxydiphthalic anhydride, 4,4'-diaminodiphenyl ether and N,N-dimethylformamide are added to a nitrogen-protected reactor and stirred, the reactor is stably heated to 80-90°C, and the reaction is kept warm for 2-3 hours, a polysiloxane solution is added to the reactor, and the reaction is kept warm for 3-5 hours, and the composite polyamic acid is obtained by post-treatment.
[0012] The synthetic reaction formula of composite amic acid is:
[0013] Where:
[0014] The synthetic reaction principle of composite amic acid is: During the reaction, the anhydride on 4,4'-oxydiphthalic anhydride undergoes a ring-opening condensation reaction with the amino group on 4,4'-diaminodiphenyl ether to form a prepolymer. Then, the anhydride on the prepolymer molecular chain undergoes a ring-opening condensation reaction with the amino group on the polysiloxane molecular chain to form a composite polyamic acid cross-linked with polysiloxane.
[0015] Furthermore, the amount ratio of the 4,4'-oxydiphthalic anhydride, 4,4'-diaminodiphenyl ether, N,N-dimethylformamide and polysiloxane solution is 31g:10g:100mL:20g, the polysiloxane solution is composed of polysiloxane and N,N-dimethylformamide in a weight ratio of 1:3, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature to obtain a composite polyamic acid solution, and the dispersion is added dropwise to the reactor containing the composite polyamic acid solution in a volume ratio of 1:2 to the dispersion. After the addition is completed, the mixture is stirred at the temperature for 20-30min, filtered, the filter cake is washed 3 times with purified water and then dried, and the filter cake is transferred to a drying oven at a temperature of 60-70°C, and vacuum dried to constant weight to obtain a composite polyamic acid.
[0016] Furthermore, the preparation method of polysiloxane is: aminopropylmethyldiethoxysilane, octamethylsilicone oil, and tetrahydrofuran are added to a reactor and stirred, the temperature of the reactor is increased to reflux, potassium hydroxide solution is added to the reactor, the reaction is kept warm for 10-12 hours, and polysiloxane is obtained by post-treatment.
[0017] The synthetic reaction formula of polysiloxane is:
[0018] The synthetic reaction mechanism of polysiloxane is: Under alkaline conditions, aminopropylmethyldiethoxysilane and octamethylsilicone oil are hydrolyzed and then polycondensed to form long polysiloxane chain segments modified with amino groups to obtain polysiloxane.
[0019] Furthermore, the amount ratio of aminopropylmethyldiethoxysilane, octamethylsilicone oil, tetrahydrofuran and potassium hydroxide solution is 1g:6g:30mL:4mL, the concentration of the potassium hydroxide solution is 2-4mol / L, and the post-treatment includes: after the reaction is completed, the solvent is evaporated under reduced pressure, the temperature of the reactor is lowered to room temperature, purified water and dichloromethane are added to the reactor, stirred at room temperature for 10-15min, allowed to stand for separation, the organic phase is washed 3 times with purified water and then transferred to a rotary evaporator with a water bath temperature of 40-50°C, and the solvent is evaporated under reduced pressure to obtain polysiloxane.
[0020] Further, the modified silica is processed by the following steps: B1. Add purified water, anhydrous ethanol, sodium silicate and dispersant into a reactor, stir rapidly at room temperature for 20-30 min, drop acetic acid solution into the reactor, adjust the pH value of the system to 7-8, keep warm and stir for 2-3 h, and post-treat to obtain crude nano-silicon dioxide; B2. Place the crude nano-silicon dioxide in a tube furnace. Under the protection of a mixed gas atmosphere, raise the temperature of the tube furnace to 500-600° C., keep the temperature for 3-5 hours, cool it down, and discharge the material to obtain nano-silicon dioxide. B3. Add nano-silicon dioxide, anhydrous ethanol and KH-560 into a reactor and stir. Raise the temperature of the reactor to 50-60°C, add the catalytic solution into the reactor, keep the temperature for 40-60 minutes, and perform post-treatment to obtain modified silicon dioxide.
[0021] The synthetic reaction mechanism of modified silica is: The catalytic solution catalyzes the hydrolysis of the siloxane bonds on KH-560 to form silanol groups, which undergo condensation reactions with active groups on the surface of nano-silica to form coating modifications, thereby preparing modified silica with alkylene oxide modifications.
[0022] Further, in step B1, the amount ratio of the purified water, anhydrous ethanol, sodium silicate and dispersant is 20mL:2-3mL:3-4g:1g, the dispersant is any one of sodium dodecyl sulfate and hexadecyltrimethylammonium bromide, the acetic acid solution is composed of 0.1-0.2mol / L acetic acid aqueous solution and 85wt% phosphoric acid in a volume ratio of 7:1, and the post-treatment includes: after the reaction is completed, suction filtration, washing the filter cake with anhydrous ethanol for 3 times and then drying, transferring the filter cake to a drying oven at a temperature of 60-70°C, and vacuum drying to constant weight to obtain nano dioxygen crude silicon dioxide; in step B2, the mixed gas is composed of hydrogen and nitrogen in a volume ratio of 1:3; in step B3, the amount ratio of the nano-silicon dioxide, anhydrous ethanol, KH-560 and the catalytic solution is 5g:50mL:2-3g:8mL, the catalytic solution is 0.2-0.5mol / L sodium hydroxide solution, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with purified water until it is neutral and then dried, the filter cake is transferred to a drying oven at a temperature of 60-70°C, and vacuum dried to constant weight to obtain modified silicon dioxide.
[0023] The present invention has the following beneficial effects: 1. The aluminum alloy profile with anti-fouling and wear-resistant coating of the present invention is prepared by reinforcing polyamic acid with polysiloxane to prepare a composite polyamic acid with a high degree of crosslinking, and then using epoxy-modified modified silica, polymethyl methacrylate and 1H,1H,2H,2H-perfluorodecyl mercaptan as additives to prepare a powder coating. Under a high temperature environment, the epoxy groups and active groups such as hydroxyl, amino, and imino groups in the surface of the pretreated profile and the powder coating molecules undergo ring-opening condensation to form a complex multi-element crosslinking network, thereby improving the adhesion strength, wear resistance, impact resistance and stain resistance of the coating. After being modified by immersion in a carbonate solution, titanic acid combines with the carboxylic acid group in the polyamic acid through reactions such as hydrolysis and condensation to form a titanium load in the polyamic acid coating. After high-temperature treatment, the loaded titanium is oxidized into titanium oxide, and the polyamic acid is cyclized to form polyamide, thereby further improving the comprehensive performance of the coating.
[0024] 2. The aluminum alloy profile with anti-fouling and wear-resistant coating of the present invention adjusts the pH of the system with a phosphorus-containing acetic acid solution, so that sodium silicate reacts with the hydrogen ions in acetic acid and phosphoric acid to generate a phosphorus-coated and modified silica precipitate. In a high-temperature mixed gas atmosphere, phosphorus element diffuses and dopes into the silicon dioxide lattice to form phosphorus doping, and introduces additional free carriers into the silicon dioxide particles, changing the electron density of the material and giving it good resistance to ultraviolet aging. It works together with the titanium dioxide on the surface of the coating to improve the material's resistance to ultraviolet aging. By modifying the surface of the silicon dioxide particles with epoxy groups, while promoting the dispersibility of the modified silicon dioxide in the powder coating, the modified epoxy groups on the surface serve as reaction anchors to increase the crosslinking degree of the coating material, thereby improving its wear resistance and impact resistance.
[0025] 3. The aluminum alloy profile with anti-fouling and wear-resistant coating of the present invention improves the internal structure of the coating by introducing polysiloxane chain segments into the composite polyamic acid molecular chain, making it more compact and uniform, reducing the pores and defects in the coating, and polysiloxane has extremely low surface energy. This low surface energy characteristic can improve the surface properties of the coating, making the coating surface more difficult to be wetted by water, thereby improving the hydrophobicity of the coating. The introduction of polysiloxane can also reduce the surface tension of the coating, weaken the adsorption capacity of the coating for oily substances, reduce oil pollution on the coating surface, and improve the cleanliness and aesthetics of the coating. In the powder coating, the thiol group on the 1H,1H,2H,2H-perfluorodecyl mercaptan molecule can condense with groups such as carbonyl to form thiol ester compounds. The 1H,1H,2H,2H-perfluorodecyl mercaptan molecular structure contains a large number of fluorine atoms, has strong electronegativity and low surface energy characteristics, and further reduces the surface energy of the coating, thereby significantly improving the hydrophobic and oleophobic properties of the coating and improving the anti-fouling performance of the coating. DETAILED DESCRIPTION
[0026] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] The polymethyl methacrylate in the present application is selected from Dongguan Hongkuo Plastic Co., Ltd., manufacturer: Dow Thailand, brand 8137. Example 1
[0028] This embodiment provides a method for preparing a powder coating for an antifouling and wear-resistant coating, comprising the following steps: S1. Preparation of modified silica 0.1 mol / L acetic acid aqueous solution and 85 wt % phosphoric acid were uniformly mixed in a volume ratio of 12:1 to obtain an acetic acid solution; Weigh: 2000mL of purified water, 200mL of anhydrous ethanol, 300g of sodium silicate and 100g of sodium dodecyl sulfate, add them into the reactor, set the speed of the reactor to 800r / min, stir for 20min at room temperature, add acetic acid solution dropwise into the reactor, adjust the pH of the system to 7, keep warm and stir for 2h, filter, wash the filter cake with anhydrous ethanol 3 times and then dry it, transfer the filter cake to a drying oven at a temperature of 60°C, and vacuum dry it to constant weight to obtain crude nano-silicon dioxide; The crude nano-silicon dioxide is placed in a tube furnace, and under the protection of a mixed gas atmosphere, the temperature of the tube furnace is raised to 500° C., and the temperature is kept for 3 hours, and then the temperature is lowered and the material is discharged to obtain nano-silicon dioxide, wherein the mixed gas is composed of hydrogen and nitrogen in a volume ratio of 1:3; Weigh: 300 g of nano-silica, 3000 mL of anhydrous ethanol and 120 g of KH-560, add them into a reactor and stir, raise the temperature of the reactor to 50°C, add 480 mL of 0.2 mol / L sodium hydroxide solution into the reactor, keep warm and react for 40 minutes, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at a temperature of 60°C, and vacuum dry it to constant weight to obtain modified silica.
[0029] S2. Preparation of polysiloxane Weigh: 50 g of aminopropylmethyldiethoxysilane, 300 g of octamethylsilicone oil, and 1500 mL of tetrahydrofuran, add them to a reactor and stir, raise the temperature of the reactor to reflux the system, add 200 mL of 2 mol / L potassium hydroxide solution to the reactor, keep the reaction for 10 hours, evaporate the solvent under reduced pressure, lower the temperature of the reactor to room temperature, add 1000 mL of purified water and 1000 mL of dichloromethane to the reactor, stir at room temperature for 10 minutes, stand and separate the liquids, wash the organic phase with purified water 3 times, transfer it to a rotary evaporator with a water bath temperature of 40°C, and evaporate the solvent under reduced pressure to obtain polysiloxane.
[0030] S3. Preparation of composite polyamic acid The polysiloxane and N,N-dimethylformamide are uniformly mixed in a weight ratio of 1:3 to obtain a polysiloxane solution; Weigh: 310 g of 4,4'-oxydiphthalic anhydride, 100 g of 4,4'-diaminodiphenyl ether and 1000 mL of N,N-dimethylformamide, add them into a nitrogen-protected reactor and stir, the reactor is stably heated to 80°C, and the temperature is kept for 2 hours, 200 g of polysiloxane solution is added to the reactor, and the temperature is kept for 3 hours. After the reaction is completed, the reactor temperature is lowered to room temperature to obtain a composite polyamide solution; Sodium lauryl sulfate and purified water were mixed uniformly at a ratio of 1 g:80 mL to obtain a dispersed solution; The dispersion was added dropwise to the reactor containing the composite amic acid solution in a volume ratio of 1:2. After the addition was completed, the mixture was stirred for 20 minutes at a temperature of 1:2 and filtered. The filter cake was washed with purified water for 3 times and then dried. The filter cake was transferred to a drying oven at 60°C and vacuum dried to constant weight to obtain a composite polyamic acid.
[0031] S4. Preparation of powder coating Weigh: 400 g of composite polyamic acid, 100 g of modified silica, 150 g of polymethyl methacrylate and 60 g of 1H,1H,2H,2H-perfluorodecyl mercaptan and add them into a ball mill. After ball milling for 12 hours, transfer them to a reactor, heat until the system is melted, cool and solidify, crush, and pass through a 300-mesh sieve to obtain a powder coating. Example 2
[0032] This embodiment provides a method for preparing a powder coating for an antifouling and wear-resistant coating, comprising the following steps: S1. Preparation of modified silica 0.15 mol / L acetic acid aqueous solution and 85 wt % phosphoric acid were uniformly mixed in a volume ratio of 12:1 to obtain an acetic acid solution; Weigh: 2000mL of purified water, 250mL of anhydrous ethanol, 350g of sodium silicate and 100g of sodium dodecyl sulfate and add them into a reactor. Set the speed of the reactor to 900r / min. Stir for 25min at room temperature. Add acetic acid solution dropwise into the reactor to adjust the pH of the system to 7.5. Keep warm and stir for 2.5h. Filter by suction. Wash the filter cake with anhydrous ethanol for 3 times and then drain. Transfer the filter cake to a drying oven at 65°C and vacuum dry to constant weight to obtain crude nano-silicon dioxide. The crude nano-silicon dioxide is placed in a tube furnace, and under the protection of a mixed gas atmosphere, the temperature of the tube furnace is raised to 550° C., and the temperature is kept for 4 hours, and then the temperature is lowered and the material is discharged to obtain nano-silicon dioxide, wherein the mixed gas is composed of hydrogen and nitrogen in a volume ratio of 1:3; Weigh: 300 g of nano-silica, 3000 mL of anhydrous ethanol and 120 g of KH-560, add them into a reactor and stir, raise the temperature of the reactor to 55°C, add 480 mL of 0.35 mol / L sodium hydroxide solution into the reactor, keep warm and react for 50 minutes, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at a temperature of 65°C, and vacuum dry it to constant weight to obtain modified silica.
[0033] S2. Preparation of polysiloxane Weigh: 50 g of aminopropylmethyldiethoxysilane, 300 g of octamethylsilicone oil, and 1500 mL of tetrahydrofuran, add them to a reactor and stir, raise the temperature of the reactor to reflux the system, add 200 mL of 3 mol / L potassium hydroxide solution to the reactor, keep the reaction for 11 hours, evaporate the solvent under reduced pressure, lower the temperature of the reactor to room temperature, add 1000 mL of purified water and 1000 mL of dichloromethane to the reactor, stir at room temperature for 13 minutes, stand and separate the liquids, wash the organic phase with purified water 3 times, transfer it to a rotary evaporator with a water bath temperature of 45°C, and evaporate the solvent under reduced pressure to obtain polysiloxane.
[0034] S3. Preparation of composite polyamic acid The polysiloxane and N,N-dimethylformamide are uniformly mixed in a weight ratio of 1:3 to obtain a polysiloxane solution; Weigh: 310 g of 4,4'-oxydiphthalic anhydride, 100 g of 4,4'-diaminodiphenyl ether and 1000 mL of N,N-dimethylformamide, add them into a nitrogen-protected reactor and stir, the reactor is stably heated to 85°C, and the temperature is kept for 2.5 hours, 200 g of polysiloxane solution is added to the reactor, and the temperature is kept for 4 hours. After the reaction is completed, the reactor temperature is lowered to room temperature to obtain a composite polyamide solution; Sodium lauryl sulfate and purified water were mixed uniformly at a ratio of 1 g:80 mL to obtain a dispersed solution; The dispersion was added dropwise to the reactor containing the composite amic acid solution in a volume ratio of 1:2. After the addition was completed, the mixture was stirred for 25 minutes at a temperature maintained at room temperature, filtered, and the filter cake was washed with purified water for 3 times and then dried. The filter cake was transferred to a drying oven at 65°C and vacuum dried to constant weight to obtain a composite polyamic acid.
[0035] S4. Preparation of powder coating Weigh: 450g of composite polyamic acid, 125g of modified silica, 175g of polymethyl methacrylate and 70g of 1H,1H,2H,2H-perfluorodecyl mercaptan and add them into a ball mill. After ball milling for 13h, transfer them to a reactor, heat until the system is melted, cool and solidify, crush, and pass through a 300-mesh sieve to obtain a powder coating. Example 3
[0036] This embodiment provides a method for preparing a powder coating for an antifouling and wear-resistant coating, comprising the following steps: S1. Preparation of modified silica 0.2 mol / L acetic acid aqueous solution and 85 wt % phosphoric acid were uniformly mixed in a volume ratio of 12:1 to obtain an acetic acid solution; Weigh: 2000mL of purified water, 300mL of anhydrous ethanol, 400g of sodium silicate and 100g of hexadecyltrimethylammonium bromide, add them into the reactor, set the speed of the reactor to 1000r / min, stir for 30min at room temperature, add acetic acid solution dropwise into the reactor, adjust the pH of the system to 8, keep warm and stir for 3h, filter, wash the filter cake with anhydrous ethanol 3 times and then drain, transfer the filter cake to a drying oven at a temperature of 70°C, and vacuum dry to constant weight to obtain crude nano-silicon dioxide; The crude nano-silicon dioxide is placed in a tube furnace, and under the protection of a mixed gas atmosphere, the temperature of the tube furnace is raised to 600° C., and the temperature is kept for 5 hours, and then the temperature is lowered and the material is discharged to obtain nano-silicon dioxide, wherein the mixed gas is composed of hydrogen and nitrogen in a volume ratio of 1:3; Weigh: 300 g of nano-silica, 3000 mL of anhydrous ethanol and 180 g of KH-560, add them into a reactor and stir, raise the temperature of the reactor to 60°C, add 480 mL of 0.5 mol / L sodium hydroxide solution into the reactor, keep warm and react for 60 minutes, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at a temperature of 70°C, and vacuum dry it to constant weight to obtain modified silica.
[0037] S2. Preparation of polysiloxane Weigh: 50 g of aminopropylmethyldiethoxysilane, 300 g of octamethylsilicone oil, and 1500 mL of tetrahydrofuran, add them to a reactor and stir, raise the temperature of the reactor to reflux the system, add 200 mL of 4 mol / L potassium hydroxide solution to the reactor, keep the reaction for 12 hours, evaporate the solvent under reduced pressure, lower the temperature of the reactor to room temperature, add 1000 mL of purified water and 1000 mL of dichloromethane to the reactor, stir at room temperature for 15 minutes, stand and separate the liquids, wash the organic phase with purified water 3 times, transfer it to a rotary evaporator with a water bath temperature of 50°C, and evaporate the solvent under reduced pressure to obtain polysiloxane.
[0038] S3. Preparation of composite polyamic acid The polysiloxane and N,N-dimethylformamide are uniformly mixed in a weight ratio of 1:3 to obtain a polysiloxane solution; Weigh: 310 g of 4,4'-oxydiphthalic anhydride, 100 g of 4,4'-diaminodiphenyl ether and 1000 mL of N,N-dimethylformamide, add them into a nitrogen-protected reactor and stir, the reactor is stably heated to 90°C, and the temperature is kept for 3 hours, 200 g of polysiloxane solution is added to the reactor, and the temperature is kept for 5 hours. After the reaction is completed, the reactor temperature is lowered to room temperature to obtain a composite polyamide solution; Sodium lauryl sulfate and purified water were mixed uniformly at a ratio of 1 g:80 mL to obtain a dispersed solution; The dispersion was added dropwise to the reactor containing the composite amic acid solution in a volume ratio of 1:2. After the addition was completed, the mixture was stirred for 30 minutes at a temperature maintained at room temperature. The filter cake was washed with purified water for 3 times and then dried. The filter cake was transferred to a drying oven at 70°C and vacuum dried to constant weight to obtain a composite polyamic acid.
[0039] S4. Preparation of powder coating Weigh: 500 g of composite polyamic acid, 150 g of modified silica, 200 g of polymethyl methacrylate and 80 g of 1H,1H,2H,2H-perfluorodecyl mercaptan and add them into a ball mill. After ball milling for 14 hours, transfer them to a reactor, heat until the system is melted, cool and solidify, crush, and pass through a 300-mesh sieve to obtain a powder coating. Example 4
[0040] This embodiment provides a method for preparing an aluminum alloy profile with an anti-fouling and wear-resistant coating, comprising the following steps: Step 1: Surface treatment The aluminum alloy profile is immersed in 2wt% nitric acid at a temperature of 55°C for 30 minutes, the aluminum alloy profile is fished out, washed with purified water until neutral, and then ultrasonically cleaned with acetone and ethanol for 20 minutes in sequence to obtain a pre-treated profile; KH-560, anhydrous ethanol and 0.2 mol / L sodium hydroxide solution were uniformly mixed in a dosage ratio of 5 g:20 mL:6 mL to obtain a KH-560 solution; The KH-560 solution was sprayed on the pre-treated profile, left at room temperature for 30 minutes, the profile surface was cleaned with purified water and then dried to obtain the pre-treated profile.
[0041] Step 2: Electrostatic spraying The powder coating prepared in Example 1 was sprayed on the surface of the pretreated profile by electrostatic powder spraying, and then transferred to a drying oven at a temperature of 140° C. and dried for 2 hours to form a polyamic acid coating with a thickness of 0.5 mm on the surface of the aluminum alloy profile.
[0042] Step 3: Preparation of antifouling and wear-resistant coating The aluminum alloy profile with polyamic acid coating was placed in an 8wt% titanic acid aqueous solution at a temperature of 40°C, soaked for 2 hours, taken out, washed three times with purified water, and placed in a tubular furnace. The temperature of the tubular furnace was increased to 270°C and kept warm for 2.5 hours to form an anti-fouling and wear-resistant coating on the surface of the aluminum alloy profile. Example 5
[0043] This embodiment provides a method for preparing an aluminum alloy profile with an anti-fouling and wear-resistant coating, comprising the following steps: Step 1: Surface treatment The aluminum alloy profile is immersed in 2wt% nitric acid at a temperature of 60°C for 40 minutes, the aluminum alloy profile is fished out, washed with purified water until neutral, and then ultrasonically cleaned with acetone and ethanol for 20 minutes in sequence to obtain a pre-treated profile; KH-560, anhydrous ethanol and 0.2 mol / L sodium hydroxide solution were uniformly mixed in a dosage ratio of 5 g:20 mL:6 mL to obtain a KH-560 solution; The KH-560 solution was sprayed on the pre-treated profile, left at room temperature for 40 minutes, and the profile surface was cleaned with purified water and then dried to obtain the pre-treated profile.
[0044] Step 2: Electrostatic spraying The powder coating prepared in Example 2 was sprayed on the surface of the pretreated profile by electrostatic powder spraying, and then transferred to a drying oven at 150° C. and dried for 2.5 hours to form a polyamic acid coating with a thickness of 0.6 mm on the surface of the aluminum alloy profile.
[0045] Step 3: Preparation of antifouling and wear-resistant coating The aluminum alloy profile with polyamic acid coating was placed in a 9wt% titanic acid aqueous solution at a temperature of 45°C, soaked for 2.5 hours, taken out, washed three times with purified water, and placed in a tubular furnace. The temperature of the tubular furnace was increased to 275°C and kept warm for 3.0 hours to form an anti-fouling and wear-resistant coating on the surface of the aluminum alloy profile. Example 6
[0046] This embodiment provides a method for preparing an aluminum alloy profile with an anti-fouling and wear-resistant coating, comprising the following steps: Step 1: Surface treatment The aluminum alloy profile is immersed in 2wt% nitric acid at a temperature of 65°C for 50 minutes, the aluminum alloy profile is fished out, washed with purified water until neutral, and then ultrasonically cleaned with acetone and ethanol for 20 minutes in sequence to obtain a pre-treated profile; KH-560, anhydrous ethanol and 0.2 mol / L sodium hydroxide solution were uniformly mixed in a dosage ratio of 5 g:20 mL:6 mL to obtain a KH-560 solution; The KH-560 solution was sprayed on the pre-treated profile, left at room temperature for 50 minutes, the profile surface was cleaned with purified water and then dried to obtain the pre-treated profile.
[0047] Step 2: Electrostatic spraying The powder coating prepared in Example 3 was sprayed on the surface of the pretreated profile by electrostatic powder spraying, and then transferred to a drying oven at 160° C. and dried for 3 hours to form a polyamic acid coating with a thickness of 0.7 mm on the surface of the aluminum alloy profile.
[0048] Step 3: Preparation of antifouling and wear-resistant coating The aluminum alloy profile with polyamic acid coating was placed in a 10wt% titanic acid aqueous solution at a temperature of 50°C, soaked for 3 hours, taken out, washed 3 times with purified water, and placed in a tubular furnace. The temperature of the tubular furnace was increased to 280°C and kept warm for 3.5 hours to form an anti-fouling and wear-resistant coating on the surface of the aluminum alloy profile.
[0049] Comparative Example 1 The difference between this comparative example and Example 6 is that when the modified silicon dioxide in the powder coating is prepared, in step S1, no phosphoric acid is added to the acetic acid solution.
[0050] Comparative Example 2 The difference between this comparative example and Example 6 is that when the modified silicon dioxide in the powder coating is prepared, in step S3, the molar ratio of 4,4'-oxydiphthalic anhydride to 4,4'-diaminodiphenyl ether is 1:1.
[0051] Comparative Example 3 The difference between this comparative example and Example 6 is that during the preparation of the modified silicon dioxide in the powder coating used, no modified silicon dioxide is added in step S4.
[0052] Comparative Example 4 The difference between this comparative example and Example 6 is that in step 3, the immersion operation of the titanic acid aqueous solution is eliminated.
[0053] Performance Test: The mass abrasion of the samples prepared in Examples 4-6 and Comparative Examples 1-4 was measured with reference to the standard GB / T 1768-2006 "Determination of abrasion resistance of paints and varnishes - Rotating rubber grinding wheel method"; The impact strength of the samples prepared in Examples 4-6 and Comparative Examples 1-4 was measured with reference to the standard GB / T 20624.2-2006 "Rapid deformation (impact resistance) test for paints and varnishes Part 2: Drop weight test (small area punch)"; The samples were exposed to light according to method A in standard GB / T 23987-2009 "Exposure to fluorescent ultraviolet light and water for artificial weathering of paint and varnish coatings", and then the degree of change of damage of the samples prepared in Examples 4-6 and Comparative Examples 1-4 was evaluated according to standard GB / T 1766-2008 "Rating method for aging of paint and varnish coatings"; The static contact angles and advancing contact angles of the samples prepared in Examples 4-6 and Comparative Examples 1-4 to water and oil were measured with reference to the standard GB / T 30447-2013 "Nanofilm Contact Angle Measurement Method". The specific test results are shown in Table 1-2 below.
[0054]
[0055] Data Analysis: Comparative analysis of the data in Tables 1-2 above shows that the mass loss of the antifouling and wear-resistant coating applied on the surface of the aluminum alloy profile of the present invention is reduced to 2.1 mg, and the impact strength reaches 3.85 kg·m. After evaluation of the UV aging exposure sample, no perceptible change is found. The static contact angle of the sample to water reaches 169.2°, and the advancing contact angle reaches 5.2°. The static contact angle to oil reaches 160.3°, and the advancing contact angle reaches 6.6°. All performance parameters are better than those of the comparative example. The data show that the present invention uses polysiloxane to reinforce polyamic acid to prepare a highly cross-linked composite polyamic acid, and then uses epoxy-modified modified silica, polymethyl methacrylate and 1H,1H,2H,2H-perfluorodecyl mercaptan as additives to prepare powder coatings. Through surface treatment, electrostatic spraying, immersion modification and high-temperature treatment, not only the wear resistance and anti-fouling properties of the aluminum alloy surface coating are effectively improved, but also its impact resistance and UV aging resistance are improved.
[0056] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing an aluminum alloy profile with an antifouling and wear-resistant coating, characterized in that: The following steps are involved: S1. Surface treatment is performed on the aluminum alloy profile to obtain a pre-treated profile; S2, adding composite polyamic acid, modified silica, polymethyl methacrylate and 1H,1H,2H,2H-perfluorodecyl mercaptan into a ball mill, transferring to a reaction kettle after ball milling for 12-14 hours, heating until the system is melted, cooling and solidifying, crushing, and passing through a 300-mesh sieve to obtain a powder coating; S3, using a powder electrostatic spraying method, spraying powder coating on the surface of the pretreated profile, transferring it to a drying oven at a temperature of 140-160°C, drying it for 2-3 hours, and forming a polyamic acid coating with a thickness of 0.5-0.7mm on the surface of the aluminum alloy profile; S4. Place the aluminum alloy profile with polyamic acid coating in a modification liquid with a temperature of 40-50°C, soak for 2-3 hours, take it out, wash the surface with purified water, and perform heat treatment to form an antifouling and wear-resistant coating on the surface of the aluminum alloy profile.
2. The method for preparing an aluminum alloy profile with an antifouling and wear-resistant coating according to claim 1, characterized in that: The surface treatment in step S1 includes the following steps: A1. Soak the aluminum alloy profile in 2wt% nitric acid at a temperature of 55-65°C for 30-50 minutes, remove the aluminum alloy profile, wash it with purified water until it is neutral, and then ultrasonically clean the aluminum alloy profile with acetone and ethanol for 20 minutes in sequence to obtain a pre-treated profile; A2. Spray the KH-560 solution on the pre-treated profile, place it at room temperature for 30-50 minutes, clean the profile surface with purified water and then dry it to obtain the pre-treated profile, wherein the KH-560 solution is composed of KH-560, anhydrous ethanol and 0.2 mol / L sodium hydroxide solution in a dosage ratio of 5g:20mL:6mL.
3. The method for preparing an aluminum alloy profile with an antifouling and wear-resistant coating according to claim 1, characterized in that: In step S2, the weight ratio of composite polyamic acid, modified silica, polymethyl methacrylate and 1H,1H,2H,2H-perfluorodecyl mercaptan is 40-50:10-15:15-20:6-8; in step S4, the modifying liquid is an 8-10wt% titanic acid aqueous solution, and the heat treatment method is: placing the aluminum alloy profile in a tubular furnace, raising the temperature of the tubular furnace to 270-280°C, and heat-insulating treatment for 2.5-3.5h.
4. The method for preparing an aluminum alloy profile with an antifouling and wear-resistant coating according to claim 1, characterized in that: The preparation method of composite polyamic acid is as follows: 4,4'-oxydiphthalic anhydride, 4,4'-diaminodiphenyl ether and N,N-dimethylformamide are added into a nitrogen-protected reactor and stirred, the reactor is stably heated to 80-90°C, and the temperature is kept for reaction for 2-3 hours, a polysiloxane solution is added into the reactor, the temperature is kept for reaction for 3-5 hours, and the composite polyamic acid is obtained by post-treatment.
5. The method for preparing an aluminum alloy profile with an antifouling and wear-resistant coating according to claim 4, characterized in that: The usage ratio of the 4,4'-oxydiphthalic anhydride, 4,4'-diaminodiphenyl ether, N,N-dimethylformamide and polysiloxane solution is 31g:10g:100mL:20g, and the polysiloxane solution is composed of polysiloxane and N,N-dimethylformamide in a weight ratio of 1:
3.
6. The method for preparing an aluminum alloy profile with an antifouling and wear-resistant coating according to claim 5, characterized in that: The preparation method of polysiloxane is as follows: aminopropylmethyldiethoxysilane, octamethylsilicone oil and tetrahydrofuran are added into a reaction kettle and stirred, the temperature of the reaction kettle is increased to reflux, potassium hydroxide solution is added into the reaction kettle, the reaction is kept warm for 10-12 hours, and polysiloxane is obtained by post-treatment.
7. The method for preparing an aluminum alloy profile with an antifouling and wear-resistant coating according to claim 6, characterized in that: The dosage ratio of the aminopropylmethyldiethoxysilane, octamethyl silicone oil, tetrahydrofuran and potassium hydroxide solution is 1g:6g:30mL:4mL, and the concentration of the potassium hydroxide solution is 2-4mol / L.
8. The method for preparing an aluminum alloy profile with an antifouling and wear-resistant coating according to claim 1, characterized in that: Modified silica is processed by the following steps: B1. Add purified water, anhydrous ethanol, sodium silicate and dispersant into a reactor, stir rapidly at room temperature for 20-30 min, drop acetic acid solution into the reactor, adjust the pH value of the system to 7-8, keep warm and stir for 2-3 h, and post-treat to obtain crude nano-silicon dioxide; B2. Place the crude nano-silicon dioxide in a tube furnace. Under the protection of a mixed gas atmosphere, raise the temperature of the tube furnace to 500-600° C., keep the temperature for 3-5 hours, cool it down, and discharge the material to obtain nano-silicon dioxide. B3. Add nano-silicon dioxide, anhydrous ethanol and KH-560 into a reactor and stir. Raise the temperature of the reactor to 50-60°C, add the catalytic solution into the reactor, keep the temperature for 40-60 minutes, and perform post-treatment to obtain modified silicon dioxide.
9. The method for preparing an aluminum alloy profile with an antifouling and wear-resistant coating according to claim 8, characterized in that: In step B1, the amount ratio of the purified water, anhydrous ethanol, sodium silicate and dispersant is 20mL:2-3mL:3-4g:1g, the dispersant is any one of sodium dodecyl sulfate and hexadecyltrimethylammonium bromide, and the acetic acid solution is composed of 0.1-0.2mol / L acetic acid aqueous solution and 85wt% phosphoric acid in a volume ratio of 7:1; in step B2, the mixed gas is composed of hydrogen and nitrogen in a volume ratio of 1:3; in step B3, the amount ratio of the nano-silica, anhydrous ethanol, KH-560 and catalytic solution is 5g:50mL:2-3g:8mL, and the catalytic solution is 0.2-0.5mol / L sodium hydroxide solution.